DAMPAK PENGGUNAAN LAHAN TERHADAP STOK KARBON DI TANAH GAMBUT: STUDI PERBANDINGAN DAN IMPLIKASI KEBIJAKAN - Ilmi, Rozatul; Hermansah; Yulnafatmawita; Yasin, Syafrimen (Departemen Tanah, Fakultas Bio-industri Pertanian dan Kehutanan, Universitas Brawijaya, 2026)
Tropical peatlands are among the largest carbon stocks on earth, but also the most vulnerable to anthropogenic disturbances. This study aims to analyze the impacts of land-use change on carbon stocks in peatlands, focusing on conversion to plantations, agriculture, and infrastructure, as well as to evaluate the effectiveness of restoration strategies and protection policies. Using a systematic review approach of 50 recent scientific publications (2010–2025), the results show that peatland conversion causes large amounts of carbon release, ranging from 70–120 tons of CO₂ per hectare per year, accompanied by land subsidence of up to 7 cm per year. Drainage and land fires are the main factors accelerating carbon emissions. In contrast, restoration efforts through rewetting and revegetation have been shown to reduce emissions by up to 65% and increase long-term carbon accumulation. The success of this strategy is greatly influenced by the biophysical conditions of the land, policy support, and local community participation. This study recommends the need for an integrated approach that includes moratoriums, economic incentives, legal strengthening, and technology-based monitoring as strategic steps in protecting carbon stocks and mitigating climate change.